Pemberdayaan Kader Gerakan Penanganan dan Pencegahan (GERCEP) KEK - Susianti Susianti; Arifa Usman; Ayu Irawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Chronic Energy Deficiency (CED) in pregnant women can cause children born with cognitive decline, risk of stunting, and risk of chronic diseases in adults. The problem of pregnant women in CED is caused by low nutritional intake. Pregnant women with anemia are at 4.13 times greater risk of giving birth to children with short birth length compared to mothers who are not anemic. CED in pregnant women can cause risks and complications including anemia, bleeding, maternal weight does not increase normally and contracting infectious diseases. CED in pregnant women can affect the growth process of the fetus and can cause miscarriage, abortion, stillbirth, neonatal death, congenital defects, anemia in infants, intrapartum asphyxia, and low birth weight (LBW). Based on a survey conducted at the Cendana Putih Health Center, 45 pregnant women experienced CED (12.4%) in 2023. The problems that occur can be overcome by holding a collaborative program that can improve the health of pregnant women. This program can be used to address problems appropriately, namely by empowering pregnant women and cadres through GerCep CED. The design used in this program is community service activities carried out in the form of education in the form of providing pocket books and conducting direct counseling during the schedule of pregnant women's classes and assistance in making PMT from local food ingredients. The conclusion of this activity is that participants who initially had a low level of knowledge of KEK in pregnant women became more knowledgeable about KEK in pregnant women.